Gut feeling about alpha-synuclein in gastro-intestinal biopsies: biomarker in the making? - Ruffmann, C; Parkkinen, L (Wiley, 2015)
In recent years, several studies have investigated the potential of immunohistochemical detection of -synuclein in the gastro-intestinal tract to diagnose Parkinson’s disease (PD). While methodological heterogeneity has hindered comparability between studies, it has become increasingly apparent that the high sensitivity and specificity reported in preliminary studies has not been sustained in subsequent large scale studies. What constitutes pathological -synuclein in the alimentary canal that could distinguish between PD patients and controls and how this can be reliably detected represent key outstanding questions in the field. In this review, we will comment on and compare the variable technical aspects from previous studies, and by highlighting some advantages and shortcomings we hope to delineate a standardized approach to facilitate the consensus criteria urgently needed in the field. Furthermore, we will describe alternative detection techniques to conventional immunohistochemistry that have recently emerged and may facilitate ease of interpretation and reliability of gastro-intestinal -synuclein detection. Such techniques have the potential to detect the presence of pathological -synuclein and include the paraffin-embedded tissue-blot, the proximity ligation assay, the protein misfolding cyclic amplification technique and the real-time quaking induced conversion assay. Finally, we will review two non-synonymous theories that have driven the enteric -synuclein research, namely that 1) -synuclein propagates in a prion-like fashion from the peripheral nervous system to the brain via vagal connections, and 2) gastro-intestinal -synuclein deposition may be used as a clinically useful biomarker in PD.